Muscle pathology of hereditary motor and sensory neuropathy with proximal dominant involvement with TFG mutation. Issue 6 (30th August 2019) - Yamashita, Satoshi; Kimura, En; Zhang, Ziwei; Tawara, Nozomu; Hara, Kentaro; Yoshimura, Akiko; Takashima, Hiroshi; Ando, Yukio
Abstract: Background: Hereditary motor and sensory neuropathy with proximal dominant involvement (HMSN‐P) is characterized by adult onset, a slowly progressive course and autosomal dominant inheritance. It remains unclear whether myopathic changes occur histopathologically. Methods: We encountered 2 patients in a family with a heterozygous p.P285L mutation in TRK‐fused gene (TFG), which is known to cause HMSN‐P. The affected individuals developed proximal‐dominant muscle weakness in their 40s, which slowly progressed to a motor neuron disease‐like phenotype. Results: Muscle biopsy showed myopathic pathology including fiber size variability, increased internal nuclei, fiber splitting, and core‐like structures, associated with neurogenic changes: large groups of atrophic fibers and fiber type‐grouping. Immunohistochemistry revealed sarcoplasmic aggregates of TFG, TDP‐43, and p62 without congophilic material. Conclusions: The present study demonstrates myopathic changes in HMSN‐P. Although the mechanisms underlying the skeletal muscle involvement remain to be elucidated, immunohistochemistry suggests that abnormal protein aggregation may be involved in the myopathic pathology. Abstract : See editorial on pages 645–647 in this issue .